Kewarisan Beda Agama di Indonesia: Harmonisasi Hukum Islam dan Hukum Perdata melalui Wasiat Wajibah - Siti Muinah; Kerwanto Kerwanto (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2026)
Religious differences between a deceased estate owner and their heirs constitute a significant issue in Indonesia's inheritance law system, as they involve the intersection of Islamic inheritance law and the national legal system. This study aims to analyze the legal status of children who convert from Islam to another religion (apostasy) within the framework of Islamic inheritance law and Indonesian positive law, as well as to examine the application of wasiat wajibah (mandatory bequest) as a legal mechanism for resolving interfaith inheritance disputes. This research employs a normative legal method using statutory, conceptual, and case approaches, supported by field research. The analysis focuses on the Decision of the Salatiga Religious Court No. 123/Pdt.P/2019/PA.Sltg, the Determination of the Badung Religious Court No. 45/Pdt.P/2020/PA.Bdg, and empirical findings from the Tangerang Religious Court. The findings reveal that religious difference constitutes a legal impediment to inheritance (mani' al-irth), as affirmed in the hadith narrated by al-Bukhārī, “Lā yarithu al-muslimu al-kāfira wa lā al-kāfiru al-muslima” (“A Muslim does not inherit from a non-Muslim, nor does a non-Muslim inherit from a Muslim”), and codified in Article 171(c) of the Compilation of Islamic Law (Kompilasi Hukum Islam). Nevertheless, judicial practice has developed the concept of wasiat wajibah through judicial precedents as a legal instrument to protect the economic rights of heirs of a different religion without recognizing them as legal heirs under Islamic law. These findings demonstrate that wasiat wajibah serves as a mechanism for harmonizing Islamic law with Indonesian positive law while promoting substantive justice in the settlement of inheritance disputes within Indonesia's pluralistic society.